Triply Differential Single Ionization of Argon: Charge Effects for Positron and Electron Impact - de Lucio, O. G. (2010)
Triply differential single ionization of Ar by 200 eV positron and electron impact is measured and calculated. For an unequivocal test of kinematic differences, fully differential ejected electron angular distributions are measured using the same experimental apparatus and conditions for both positron and electron impact. The binary/recoil intensity ratios are shown to significantly differ for the two projectiles. These data are used to test theoretical calculations.